Levonorgestrel intrauterine system in menorrhagia-an effective and acceptable alternative - Bafna, Barkha A.; Bafna, Amit N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To study the efficacy, performance and acceptability of levonorgestrel intrauterine device (LNG-IUS) in treatment of women with menorrhagia. Methods: This was a descriptive, prospective and observational study conducted over a period of January 2015 to September 2020. Seventy-five (75) women presented with heavy menstrual bleeding having no contraindication for device underwent LNG-IUS insertion after consent. Menstrual pattern, pictorial blood loss assessment chart score (PBAC), rate of acceptability and satisfaction were recorded at 3 months, 6 months, 1, 2 and 3 years after insertion of LNG-IUS. Results: The most common bleeding pattern at 3 month post-insertion was inter-menstrual spotting followed by infrequent menses, oligomenorrhea and amenorrhea. LNG-IUS caused 45.19% reduction in menstrual blood loss (MBL) at 3 months, 81.48% at 1 year, 91.85% at 2 years and 97% at 3 years. Hemoglobin levels improved from mean baseline 8.9 mg/l to 12.8 mg/l at 3 years. Majority of women were satisfied with this minimally-invasive treatment with continuation rate of 94.66%. No major side-effects were noted. Conclusions: LNG-IUS is an excellent minimal invasive, highly effective in controlling blood loss and well-tolerated alternative for women with menorrhagia. Its fertility-sparing property makes it an emerging option for young women.